The Effect of Burning Temperature On Rice Husk From Pasir Puteh And Pasir Tumboh Areas, Kelantan - AHMAD, SUFIZAR; MOHD HISHAM, MOHAMAD HAZIQ AFFIF; ABDUL SHUKOR, MUHAMMAD SYAHMIE SUFI (Research Progress in Mechanical and Manufacturing Engineering, 2023)
In this study, among the locations taken to see in terms of differences in element composition are in Pasir Puteh and Pasir Tumboh, Kelantan. The samples were divided into five samples according to location with temperatures of 550°C, 650°C, 750°C, 850°C and 950°C. Sintering method by using sintering profile according to the respective temperature in the furnace machine. The analysis performed is the analysis of microstructure, element composition, thermogravimetric and molecular. Ten burnt samples and two raw samples will be involved in this analysis. In conclusion, samples from Pasir Puteh and Pasir Tumboh can be compared in terms of microstructure, element composition, weight reduction and molecular content.